1986
DOI: 10.1080/00071668608416864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of luteinising hormone releasing hormone and its analogues on plasma luteinising hormoneconcentrations in incubating bantam hens

Abstract: The ability of synthetic vertebrate luteinising hormone releasing hormones (LHRHs) and their long-acting analogues to maintain elevated plasma luteinising hormone (LH) concentrations and to stimulate ovarian growth was investigated in incubating bantam hens. Chicken LHRH-II (pGlu1-His2-Trp3-Ser4-His5-Gly6-Trp7-Tyr8-Pro9-G ly10-NH2) was more effective than chicken LHRH-I (pGlu1-His2-Trp3-Ser4-Tyr5-Gly6-Leu7-Gln8-Pro9-Gly10-N H2) or porcine LHRH (pGlu1-His2-Trp3-Ser4-Tyr5-Gly6-Leu7-Arg8-Pro9-Gly10-N H2) in stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The pituitary of incubating turkey hens and chickens release more LH in response to LHRH stimulation than pituitaries of laying birds [present study, 6,7], The enhanced pituitary re sponse of the incubating hen to the LHRH challenge appears to result from diminished ovarian inhibitory influence on the pituitary. This is substantiated by the findings that the peak LH response to LHRH was similar for sham-operated and Ovx incubating birds and that the peak LH response of laying hens increased to that of incu bating birds following Ovx ( fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The pituitary of incubating turkey hens and chickens release more LH in response to LHRH stimulation than pituitaries of laying birds [present study, 6,7], The enhanced pituitary re sponse of the incubating hen to the LHRH challenge appears to result from diminished ovarian inhibitory influence on the pituitary. This is substantiated by the findings that the peak LH response to LHRH was similar for sham-operated and Ovx incubating birds and that the peak LH response of laying hens increased to that of incu bating birds following Ovx ( fig.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, exogenous oPrl fails to totally abolish the ovariectomy (Ovx)-induced increases in LH secretion in the turkey [4], These results taken together with the findings that the Ovx-induced LH rise in incubating turkeys occurs only after ND, a procedure known to reduce circulating Prl [5], suggest that both nesting stimulus and elevated Prl are of importance in the complete suppression of LH levels in incubating birds [4], An alternative explanation may be that the depressed peripheral LH in the hyperprolactinemic incubating tur key is partially dependent on the ovary. Recently, it has been shown that the LH releasing mechanism is enhanced [6,7] whereas the LHp gene expression is depressed [8] during incubation.…”
Section: Introductionmentioning
confidence: 99%
“…After hens are de prived of nest and eggs, or the eggs hatch, incubation behavior ceases and the changes in LH and prolactin secretion are reversed within 48-72 h [3][4][5]. The reduc tion in plasma LH in birds at the onset of incubation is not caused by a loss of responsiveness of the gonadotropes to gonadotropin-releasing hormone (GnRH) [ 1,6,7] and is probably caused by a reduction in the release of chicken GnRH-I (cGnRH-1) from the hypothalamus. As in most nonmammalian vertebrates two forms of GnRH exist in chickens, cGnRH-1 and cGnRH-Il [8], Of the two forms, cGnRH-I is the form that is directly involved in control ling reproduction in the domestic chicken [9], Observa tions in chickens [10,11] and turkeys [12,13] suggest that hypothalamic cGnRH-I peptide may either decrease or remain the same after the onset of incubation.…”
Section: Introductionmentioning
confidence: 99%
“…These cyclic changes are partially caused by alteration in the rate of androgen biosynthesis by Leydig cells. Androgen biosynthesis in the Leydig cells during seasonal cycle is regulated by the level of LH in the circulation and capacity of Leydig cells to respond to LH (Sharp et al, 1986). It has been reported that testosterone levels changed in parallel with spermatogenic activity in the testis.…”
Section: Resultsmentioning
confidence: 99%